(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Schistosomiasis is a neglected infectious disease that is endemic in resource-constrained settings. Nigeria has the highest cases of schistosomiasis in sub-Sahara Africa with about 29 million infected. This study was carried out with the aim to identify some risk factors of schistosomiasis and as well assess the efficacy of some urine physical parameters for a rapid screening procedure. Terminal urine samples were collected, analyzed with reagent strips and centrifuged at 400 revolution per minute for 4 minutes. Microscope (x10 objective) was used to examine and count the eggs. Raw data were imported into Epi Info software (version 7.1.2.0) from Microsoft Excel 2010 for analyses. About 357 respondents with a mean age of 9.39Â±2.06 years were sampled. Overall prevalence and intensity were 10.36% (7.61-13.96) and 322.2 eggs/10ml of urine samples respectively. Males had a higher prevalence [15.42% (10.86-20.97)] and mean intensity [77.5 eggs/10ml] and were 6 times more likely to be infected [COR (95% CI): 6.31 (2.17-25.09)]. Age group 11-15 years recorded higher prevalence (19.39% [12.10-28.61]) and intensity (110.9 eggs/10ml) and was 3 times [COR (95% CI): 3.21 (1.51-6.84)] more likely to be infected. Urine samples with faint yellow colour recorded the highest prevalence of 13.67% (8.43-20.52) and were 4 times [COR (95% CI): 4.33 (1.12-28.39)] more liable to infestation compared to the colourless samples. Age and gender are risk factors with faint yellow colour as the only reliable rapid diagnostic index. Provision of potable water and treatment with Praziquantel should be done urgently.